2018
DOI: 10.1007/s10494-018-9891-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Streamwise Vortex Generators for Flow Separation Control on Trucks

Abstract: An experimental study of the effect of Dielectric Barrier Discharge plasma actuators on the flow separation on the A-pillar of a modern truck under cross-wind conditions has been carried out. The experiments were done in a wind tunnel with a 1:6 scale model of a tractor-trailer combination. The actuators were used as vortex generators positioned on the A-pillar on the leeward side of the tractor and the drag force was measured with a wind-tunnel balance. The results show that the effect at the largest yaw angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In particular, many studies focusing on improvement of wing performance by suppressing the flow separation (Sato et al, 2015;Fujii, 2018) have been conducted in the aerospace field. Regarding applications of PA on automobile flow, aerodynamic noise reduction (Miyamoto et al, 2018) and aerodynamic drag reduction (Shadmani et al, 2018;Kanatani et al, 2009;Vernet et al, 2018) have been studied. These studies aimed to reduce the boundary layer separation from the automobile's body, such as at the roof's end or the rounded pillar, similar to suppressing flow separation on a wing.…”
Section: Aerodynamic Drag Reduction Of a Simplified Vehicle Model By mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, many studies focusing on improvement of wing performance by suppressing the flow separation (Sato et al, 2015;Fujii, 2018) have been conducted in the aerospace field. Regarding applications of PA on automobile flow, aerodynamic noise reduction (Miyamoto et al, 2018) and aerodynamic drag reduction (Shadmani et al, 2018;Kanatani et al, 2009;Vernet et al, 2018) have been studied. These studies aimed to reduce the boundary layer separation from the automobile's body, such as at the roof's end or the rounded pillar, similar to suppressing flow separation on a wing.…”
Section: Aerodynamic Drag Reduction Of a Simplified Vehicle Model By mentioning
confidence: 99%
“…These studies aimed to reduce the boundary layer separation from the automobile's body, such as at the roof's end or the rounded pillar, similar to suppressing flow separation on a wing. Vernet et al (2018) mounted a PA in a U-shape configuration to induce a longitudinal vortex to suppress the flow separation at the rounded pillar surface. Conversely, the aerodynamic drag of an automobile can also be reduced by promoting flow separation on the body surface.…”
Section: Aerodynamic Drag Reduction Of a Simplified Vehicle Model By mentioning
confidence: 99%
“…24 presumably saturates because h should be longer for larger airspeeds. Similar considerations about scaling the size of the actuators has been done also in other studies applied to ground vehicles [38]. At present the scaling problem is open, and recently an attempt to follow these design rules at larger airspeeds has been done by testing a multi-tip DBD of larger size with encouraging results up to 35 m/s [37].…”
Section: Discussionmentioning
confidence: 67%
“…They suggested that by increasing the plasma voltage, the drag reduction in high velocities can be improved. Vernet et al 39 conducted wind-tunnel experiments to control the flow separation around a truck under cross-wind conditions using DBD plasma actuators, and could obtain up to 20% drag reduction for the largest yaw angle.…”
Section: Introductionmentioning
confidence: 99%